2016
DOI: 10.1159/000443733
|View full text |Cite
|
Sign up to set email alerts
|

Sichuan Snub-Nosed Monkeys (Rhinopithecus roxellana) Consume Cicadas in the Qinling Mountains, China

Abstract: There is limited information on insectivory in folivorous primates. Here, we report that wild Sichuan snub-nosed monkeys (Rhinopithecus roxellana) consume cicadas (Karenia caelatata) in the Qinling Mountains of China. Our research suggests that snub-nosed monkeys expand their diet and prey on cicadas during summer and early autumn, possibly in response to increased availability of these insects and their relatively high protein and fat content relative to leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Observations were conducted on Sichuan snub-nosed monkeys on the southern slopes of the Qinling Mountains near Longcaoping Village in Guanyinshan National Nature Reserve (107°51′-108°01′E, 33°35′-33°45′N), Shaanxi province, central China 28 30 . The study group has been habituated to researchers since 2010 and can be observed at close range, with individual recognition based on various physical characteristics 28 30 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations were conducted on Sichuan snub-nosed monkeys on the southern slopes of the Qinling Mountains near Longcaoping Village in Guanyinshan National Nature Reserve (107°51′-108°01′E, 33°35′-33°45′N), Shaanxi province, central China 28 30 . The study group has been habituated to researchers since 2010 and can be observed at close range, with individual recognition based on various physical characteristics 28 30 .…”
Section: Methodsmentioning
confidence: 99%
“…These monkeys live in temperate forests on mountain plateaux in central and southwestern China, at 1500–3400 m. They are described as living in a multi-level society, consisting of several one-male units (OMU) and associated all-male units (AMU) 23 27 . Overall, the group has 50–150 individuals, with each OMU having a single resident adult male, several adult and sub-adult females, juveniles and infants 24 30 . Within this society the monkeys have multiple levels of social interactions and relationships 23 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidently, precursors with higher Si content may be advantageous for obtaining higher yields of ncSi. Indeed, silicon nanoclusters formed in silicon monoxide (SiO) films [16][17][18][19] and other silicon sub-oxide (SiO x , x < 2) films, [20][21][22][23] usually prepared via thermal, plasma, and laser deposition, have been of interest in optical physics for applications as protective layers 24,25 and in silicon based optoelectronics. 26 Notably, SiO is also commercially available as powders in bulk quantities having a structure and properties that appears to be different from thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Given the lower primary production of montane forests compared to forests at lower elevations with a different species composition [Whitten et al, 1996] population densities of primates on Java are lower at higher altitudes [Sugarjito et al 1997;Nijman, 2015]. The difference in structure and species composition between lowland and hill forest and montane forest reflects itself in pronounced differences in the diet of P. comata [Kavana et al, 2015;Yang et al, 2016]. Ruhiyat [1983] found the species to be largely folivorous at altitudes between 1,400 and 1,650 m a.s.l., with 65.2% of the diet comprising leaves and flowers (59.1% young leaves; 5.6% mature leaves, 7% flowers) and only 14.2% comprising fruits and seeds (13.5% fruit, 0.7% seeds).…”
Section: Discussionmentioning
confidence: 99%